The playing as resource for the pediatric nursing care in the venous puncture - Cunha, Gabriela Lopes; Silva, Liliane Faria da (Rev Rene, 2012)
We aimed to understand the effects of the playing in the peripheral venous puncture of hospitalized preschool child in the companion's perception and analyze the benefits of the playing inclusion in the nursing care to the preschool child in the companion's perception. A qualitative research carried out in an infirmary of a Pediatric Hospital of Niterói-RJ, Brazil. The subjects were seven mothers. Data collection happened in February and March 2011, it consisted of orientation with the use of a puppet, about the venous puncture procedure and a semi-structured interview in which the companions expressed their perceptions about the playing use. The following thematic units emerged: companions' opinion on the playing use; companions' perception on the effects of the playing use on the child; the importance of the use of playing activity in the care to hospitalized child. The success of the puppet use offers support for interventions of this nature.